A Social-ecological Network Analysis for Understanding Small-scale Fisheries Management in Sukabumi Coastal, West Java Province, Indonesia - Fitria Dewi Raswatie; Luky Adrianto; Ngoc Duy Nguyen (BIO Web of Conferences)
In Sukabumi Regency, West Java Province, fishing is dominated by small-scale fishers who rely on it for their livelihoods. Environmental changes affect fishing activities, leading to unstable incomes and broader socio-economic impacts. Managing small-scale fisheries is challenging due to the complex social, economic, and ecological contexts. As social-ecological systems (SES), small-scale fisheries require management that considers the resource system, its units, and the actors depending on them. Understanding the interdependent relationships within these systems is crucial. This study analyzes the social-ecological system (SES) of small-scale fisheries in the Sukabumi Coastal area using Social-Ecological Network Analysis (SENA). The analysis identifies key variables that influence the network : Regulations, Landing Spot, Coastal Area, and National Government. The results reveal a synergy between the resource system (RS), resource unit (RU), resource actor (RA), and resource governance (RG), which is essential for creating optimal and sustainable management of small-scale fisheries in Sukabumi Coastal, West Java Province.